2014
DOI: 10.1111/head.12306
|View full text |Cite
|
Sign up to set email alerts
|

Headache in Autoimmune Diseases

Abstract: Autoimmune diseases are a group of heterogeneous inflammatory disorders characterized by systemic or localized inflammation, leading to ischemia and tissue destruction. These include disorders like systemic lupus erythematosus and related diseases, systemic vasculitides, and central nervous system (CNS) vasculitis (primary or secondary). Headache is a very common manifestation of CNS involvement of these diseases. Although headache characteristics can be unspecific and often non-diagnostic, it is important to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…The majority of headaches resolve over time, independent of lupus-specific therapies [31]. Other studies found no association between migraine and SLE disease activity, biochemical or immunological markers and cerebral white matter hyperintensities [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of headaches resolve over time, independent of lupus-specific therapies [31]. Other studies found no association between migraine and SLE disease activity, biochemical or immunological markers and cerebral white matter hyperintensities [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The headache is more commonly described in some diseases (e.g., giant cell arteritis and primary central nervous system vasculitis) and is mainly reported at the onset of the disease; the characteristic is often not specific, raising important diagnostic problems [25].…”
Section: Headache In Autoimmune Disordersmentioning
confidence: 99%
“…2,6 Thunderclap headache, which is severe intensity headache that reaches maximum intensity very rapidly usually in less than 1 minute is almost never associated with PACNS. 7 This feature helps to clinically distinguish PACNS from one of its close mimics reversible cerebral vasoconstriction syndrome (RCVS). Stroke and transient ischemic attacks involving multiple vascular territories occur in 30 to 50% of patients with PACNS.…”
mentioning
confidence: 99%